Development and factor structure of the teaching approach scale - Reho, Matteo; Costa, Sara; Pirchio, Sabine; Limone, Pierpaolo; Fuccio, Raffaele Di; Gennaro, Alessandro (Frontiers in Education, 2024)
The study presents the development and factor structure of the Teaching Approach Scale (TAS), a tool aimed at assessing teaching approaches in educational settings. Literature emphasizes the significance of collaboration and a student-centered approach in enhancing learning environments. However, the translation of these approaches into daily practices faces challenges due to entrenched traditions and individual perspectives. The TAS addresses this gap by assessing educators' perspectives on teaching approaches. Exploratory and confirmatory factor analyses carried on a sample of 642 teachers revealed four dimensions defining learning approaches: (a) Development of students' autonomy, (b) Comparison and synergy in the teacher's group, (c) Development of the student as a person, and (d) Standardization of teaching. The TAS serves as a valuable instrument for capturing teachers' perspectives on teaching, thereby offering valuable insights for enhancing teaching practices and fostering professional development. Further studies need to face TAS validity and reliability, nevertheless, this study underscores the importance of considering teacher learning cultures in improving educational procedures, highlighting the role of individual perspectives in shaping teaching practices and learning environments.